2020
DOI: 10.11152/mu-2501
|View full text |Cite
|
Sign up to set email alerts
|

The value of S-Detect in improving the diagnostic performance of radiologists for the differential diagnosis of thyroid nodules

Abstract: Aims: To compare the diagnostic value of S-Detect (a computer aided diagnosis system using deep learning) in differentiating thyroid nodules in radiologists with different experience and to assess if S-Detect can improve the diagnostic performance of radiologists.Materials and methods: Between February 2018 and October 2019, 204 thyroid nodules in 181 patients were included. An experienced radiologist performed ultrasound for thyroid nodules and obtained the result of S-Detect. Four radiologists with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Wei Q et al found that S-detect can improve diagnostic performance for less experienced radiologists, and the sensitivity and specificity of S-detect are 91.3% and 65.2%, respectively ( Wei et al, 2020 ). Kim HL et al evaluated the diagnostic performance of S-Detect 1 and S-Detect 2 for detecting thyroid cancers and found that the sensitivity and specificity of S-Detect 1 are 80.2% and 82.6% and that of S-Detect 2 are 81.4% and 68.2%, respectively ( Kim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei Q et al found that S-detect can improve diagnostic performance for less experienced radiologists, and the sensitivity and specificity of S-detect are 91.3% and 65.2%, respectively ( Wei et al, 2020 ). Kim HL et al evaluated the diagnostic performance of S-Detect 1 and S-Detect 2 for detecting thyroid cancers and found that the sensitivity and specificity of S-Detect 1 are 80.2% and 82.6% and that of S-Detect 2 are 81.4% and 68.2%, respectively ( Kim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…S-thyroid, similar to S-detect, is a computer-aided diagnostic software for ultrasound identification and differentiation of benign and malignant thyroid nodules. Some studies have investigated the diagnostic value of S-detect (Samsung Medison Co., Seoul, South Korea) for benign and malignant thyroid nodules ( Choi et al, 2017 ; Kim et al, 2019 ; Xia et al, 2019 ; Barczyński et al, 2020 ; Wei et al, 2020 ), but no studies have been done on the diagnostic accuracy of S-thyroid for thyroid nodules. What is more, whether it is S-detect or S-thyroid, their diagnoses are based on a single ultrasound image.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the neural network that was used in our study to classify thyroid nodules, several other approaches using computer-aided diagnosis systems (CAD) have been evaluated. Wei et al [ 25 ] compared the diagnostic value of S-Detect, a CAD system used to differentiate benign and malignant thyroid nodules by radiologists with different levels of experience. They reported that S-Detect had an accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 77.0, 91.3, 65.2, 68.3, and 90.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, we further reviewed the integrity of the content and data of the paper, and then excluded 6 papers. In the current meta-analysis, a total of 17 studies were used [7][8][9][10][13][14][15][16][17][18][19][20][21][22][23][24][25]. In Fig 1 of this paper, the selection method and main steps of the article are described in detail.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%